Main factors of economic, land, and environmental impact due to rapid technological advancements - Nazarenko, V. (Land Management, Cadastre and Land Monitoring, 2025)
Industry 4.0 has brought transformative changes across economic, environmental, and land use dimensions, driving innovations through IoT, AI, and cloud computing technologies. This revolution fosters economic growth, promotes circular economies, and integrates renewable energy technologies. However, these advancements present challenges, including rising e-waste, energy demands, and socio-economic disparities. The study uses a qualitative research approach, synthesizing insights from recent literature and employing comparative analysis. Sources include peer-reviewed articles, case studies, and industry reports focusing on the impacts of Industry 4.0 on urbanization, sustainability, and economic growth. Data from these studies have been analyzed to identify trends, challenges, and actionable solutions.Industry 4.0 facilitates the development of new business models and improves operational efficiency through interconnectivity and analytics. Renewable energy technologies, precision agriculture, and real-time emissions monitoring showcase the environmental potential of this revolution. However, the reliance on data centers and rare earth resources highlights the ecological challenges. Figures in the article illustrate Industry 4.0’s cross-industry impacts and propose frameworks for sustainable production processes. Research materials provide details on the contributions of Industry 4.0 in enabling circular economies and improving resource management.Policymakers and businesses must address the dual nature of Industry 4.0 by implementing e-waste regulations, investing in renewable energy, and ensuring equitable socio-economic benefits. Future research should focus on scalable energy storage, urban planning innovations, and reducing disparities between large corporations and SMEs. Industry 4.0 is reshaping global systems, offering immense potential for sustainable development. Achieving this requires a balanced approach that aligns technological advancements with ecological and social responsibilities.Keywords: urbanization, industry 4.0, environmental impact, economic growth, technological footprint, economics.
Keywords: urbanization, industry 4.0; environmental impact; economic growth; technological footprint; economics